PENERAPAN MODEL PEMBELAJARAN PROYEK (PROJECT BASED LEARNING) BERBANTUAN CLAY UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS XI MIPA 5 SMA NEGERI 1 SEMARAPURA SEMESTER GANJIL TAHUN PELAJARAN 2015/2016 - Tirtawati, Ni Luh Ratna (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
This research aims to know Project Based Learning to increase biology learning outcome to the students of XI MIPA 5 of SMA Negeri 1 Semarapura in the even semester in the school year 2015/2016. The research subject are 38 students, research objects include biology lesson learning outcome. The research is carried out into two cycles consists of four (4) stages, those area: 1) Planning, 2) action realization, 3) Observation and evaluation, and 4) reflection. Cycle one (I) is carried out the main respiration system, while cycle two (II) is given the main reproduction system, for cycle one and two are planned (six) hours lesson (three times face to face teaching and learning process). The result of biology learning is also increases from cycle one to cycle two with the average 70.53 becomes 85.26 with the total percentage 55,26 % becomes 94,74 % the result of biology lesson is also increasing from cycle one to cycle two. So the conclusion of this research is that PjBL can increase of biology to the students of XI IPA 5 SMA Negeri 1 Semarapura.